MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI PONDOK PESANTREN IBNUL AMIN PAMANGKIH PUTERI - Miranti Miranti (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This thesis aims to determine the process of human resource management to improve the quality of education at the Ibnul Amin Pamangkih Putri Islamic Boarding School. Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System states that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, morals noble character, as well as the skills needed by himself, the community, the nation and the state. Human resource management is the process of planning, organizing, implementing, and controlling the Board of Islamic Boarding Schools in improving human resources in the Ibnul Amin Pamangkih Puteri Islamic Boarding School by seeing a progress in the form of increasing achievements achieved by the female students or setbacks related to the economic problems experienced by the Ibnul Amin Pamangkih Puteri Islamic Boarding School which includes activities to identify problems, make comparisons between the past and the present, and in the future, as well as carry out target/program setting activities to improve human resources. This activity is carried out so that human resource development can run smoothly, therefore what is being studied is the field of human resource development which includes teachers and education staff. Several steps of training programs have been provided so that the development of human resources at the Islamic boarding school is increased. With the aim of improving the quality of teachers, educational staff and management of Islamic boarding schools in order to grow and develop their potential so that they can provide quality and quality services to their female students. The purpose of this study is to explain human resource management to improve the quality of education at the Ibnul Amin Pamangkih Puteri Islamic Boarding School and to describe the obstacles in human resource management to improve the quality of education at the Ibnul Amin Pamangkih Puteri Islamic Boarding School. As for the type and approach to this research, it uses field research and a qualitative research approach. The subjects for this thesis research were the head of the Islamic boarding school education sector, the head of the general education sector and a number of teachers, both teaching and educational staff, who were at the Ibnul Amin Pamangkih Puteri Islamic Boarding School. The technique of collecting data in this thesis research is to use an interview, interview, and observation model which was carried out at the Ibnul Amin Pamangkih Puteri Islamic Boarding School.